The effect of mesenchymal stem cells improves the healing of burn wounds: a phase 1 dose-escalation clinical trial. (August 2022) - Schulman, Carl I; Namias, Nicholas; Pizano, Louis; Rodriguez-Menocal, Luis; Aickara, Divya; Guzman, Wellington; Candanedo, Ambar; Maranda, Eric; Beirn, Audrey; McBride, Jeffrey D; Badiavas, Evangelos V
Background: Stem cell therapy holds promise to improve healing and stimulate tissue regeneration after burn injury. Preclinical evidence has supported this; however, clinical studies are lacking. We examined the application of bone marrow-derived mesenchymal stem cells (BM-MSC) to deep second-degree burn injuries using a two-dose escalation protocol. Methods: Ten individuals aged 18 years or older with deep second-degree burn wounds were enrolled. The first five patients were administered 2.5 × 10³ BM-MSC/cm 2 to their wounds. After safety of the initial dose level was assessed, a second group of five patients was treated with a higher concentration of 5 × 10³ allogeneic BM-MSC/cm 2 . Safety was assessed clinically and by evaluating cytokine levels in mixed recipient lymphocyte/donor BM-MSC reactions (INFγ, IL-10 and TNFα). At each visit, we performed wound measurements and assessed wounds using a Patient and Observer Scar Assessment Scale (POSAS). Results: All patients responded well to treatment, with 100% closure of wounds and minimal clinical evidence of fibrosis. No adverse reactions or evidence of rejection were observed for both dose levels. Patients receiving the first dose concentration had a wound closure rate of 3.64 cm 2 /day. Patients receiving the second dose concentration demonstrated a wound closure rate of 10.47 cm 2 /day. The difference in healing rates between the two groups was not found to be statistically significant ( P  = 0.17). Conclusion: BM-MSC appear beneficial in optimising wound healing in patients with deep second-degree burn wounds. Adverse outcomes were not observed when administering multiple doses of allogeneic BM-MSC. Lay Summary: Thermal injuries are a significant source of morbidity and mortality, constituting 5%–20% of all injuries and 4% of all deaths. Despite overall improvements in the management of acutely burned patients, morbidities associated with deeper burn injuries remain commonplace. Burn patients are too often left with significant tissue loss, scarring and contractions leading to physical loss of function and long-lasting psychological and emotional impacts. In previous studies, we have demonstrated the safety and efficacy of administering bone marrow-derived mesenchymal stem cells (BM-MSC) to chronic wounds with substantial improvement in healing and evidence of tissue regeneration. In this report, we have examined the application of BM-MSC to deep second-degree burn injuries in patients. The aim of the present phase I/II clinical trial was to examine the safety and efficacy of administering allogeneic BM-MSC to deep second-degree burns. We utilised two different dose levels at concentrations 2.5 × 10 3 and 5 × 10 3 cells/cm 2 . Patients with deep second-degree burn wounds up to 20% of the total body surface area were eligible for treatment. Allogeneic BM-MSC were applied to burn wounds topically or by injection under transparent film dressing <7 days after injury. Patients were followed for at least six months after treatment. Using two dose levels allowed us to gain preliminary information as to whether different amounts of BM-MSC administered to burn wounds will result in significant differences in safety/ clinical response. Once the safety and dose-response analysis were completed, we evaluated the efficacy of allogeneic stem cell therapy in the treatment of deep second-degree burn wounds. In this study, we examined the role of allogeneic BM-MSC treatment in patients with deep second-degree burn injuries, in a dose-dependent manner. No significant related adverse events were reported. Safety was evaluated both clinically and by laboratory-based methods. Efficacy was assessed clinically through evidence of re-pigmentation, hair follicle restoration and regenerative change. While these findings are encouraging, more studies will be needed to better establish the benefit of BM-MSC in the treatment of burn injuries.